Exploring the Moorish and Mughal Styles of Colonial Buildings in Malaysia - Mohd Aliff Izuan Md Yasin; Nor Syahila Ab Rashid; Noor Hayati Ismail; Athika Norlaili Abdul Halim (Universiti Islam Melaka (UNIMEL), 2024)
Jurnal Tuah Jilid 4 Bil. 1 (page :1 - 17)